2022
DOI: 10.3390/ijms232113618
|View full text |Cite
|
Sign up to set email alerts
|

Dynamin-like Protein 1 (DNML1) as a Molecular Target for Antibody-Based Immunotherapy to Treat Glaucoma

Abstract: Slow and progressive loss of retinal ganglion cells (RGCs) is the main characteristic of glaucoma, the second leading cause of blindness worldwide. Previous studies have shown that impaired mitochondrial dynamics could facilitate retinal neurodegeneration. Mitochondrial dynamics are regulated directly (fission) or more indirectly (fusion) by dynamin-like protein 1 (DNML1). Therefore, DNM1L might be a promising target for an antibody-based approach to treat glaucoma. The consequences of targeting endogenous DNM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 122 publications
0
1
0
Order By: Relevance
“…By assessing proteomic changes in human glaucomatous retina samples, Funke et al demonstrated that the levels of a plethora of proteins are altered in glaucoma ( Funke et al, 2016 ). Further, while studies have been published on large-scale proteomics studies pertaining to protein expression at the onset of central nervous system (CNS) neuron injury ( Tonner et al, 2022 ), the PTMome of RGCs in neurodegenerative diseases is largely unknown. Liu et al and Lukas et al each assessed phosphoproteomic changes in mouse total retina lysate following optic nerve injury ( Lukas et al, 2009 ; Liu et al, 2020 ).…”
Section: Posttranslational Modifications In Glaucoma and Models Of Re...mentioning
confidence: 99%
“…By assessing proteomic changes in human glaucomatous retina samples, Funke et al demonstrated that the levels of a plethora of proteins are altered in glaucoma ( Funke et al, 2016 ). Further, while studies have been published on large-scale proteomics studies pertaining to protein expression at the onset of central nervous system (CNS) neuron injury ( Tonner et al, 2022 ), the PTMome of RGCs in neurodegenerative diseases is largely unknown. Liu et al and Lukas et al each assessed phosphoproteomic changes in mouse total retina lysate following optic nerve injury ( Lukas et al, 2009 ; Liu et al, 2020 ).…”
Section: Posttranslational Modifications In Glaucoma and Models Of Re...mentioning
confidence: 99%
“…P62-mediated mitophagy inducer (PMI) is another promising neuroprotective agent that inhibits KEAP1 and activates NF-E2-related factor 2 (NRF2), leading to the expression of antioxidant genes, including sequestosome 1 (p62/SQSTM1), and enhanced mitophagy [239]. DRP1 may also serve as an auspicious target for a potential antibody-based therapy for glaucoma, since intravitreal injection of an anti-DRP1 antibody in an animal glaucoma model protected RGCs, decreased apoptosis as shown using western blot analysis, and improved retinal functionality as observed using electroretinography [240].…”
Section: Mitophagy As a Therapeutic Targetmentioning
confidence: 99%